Analysis The Effect of The Distance Between Concrete Floating Breakwater With Double Configuration On The Mooring Line Force In Catenary System Using Dualsphysics - Yolanda, Noris; Armono, Haryo Dwito; Wahyudi (Department of Ocean Engineering, 2025)
Ports are crucial infrastructure supporting a nation’s economy. However, port utilization in Indonesia remains suboptimal due to high sea waves that can damage infrastructure and disrupt operations. A solution is the construction of Floating Breakwaters (PGA). This study analyzes the effect of spacing between dual configured concrete PGAs on mooring rope forces using a catenary system. The Smoothed Particle Hydrodynamics (SPH) method with DualSPHysics software was used to determine maximum stress on the mooring ropes. Results show that PGA spacing influences mooring tension. In variant A, spacing from 20 30 cm reduces the force by 20%, while 30–40 cm increases it by 1%. In variant B, spacing from 50–75 cm increases tension by 8%, while 75 cm–1 m decreases it by 16%. Wave height and period also affect tension. The maximum force for variant A with a single configuration occurs at a wave height of 0.18 m and a period of 2.21 s, reaching around 185 kN at the anchor and 188 kN at the fairlead. For variant B, the maximum is at a height of 0.28 m and a period of 2.84 s, reaching about 360 kN. In dual configuration, maximum force occurs at 0.2 m spacing for variant A and 0.5 m for variant B.